Cholesterol metabolic enzyme Ggpps regulates epicardium development and ventricular wall architecture integrity in mice. (24th March 2021) - Zheng, Feng; Chen, Zhong; Tang, Qiao-Li; Wang, Xin-Ying; Chong, Dan-Yang; Zhang, Tong-Yu; Gu, Ya-Yun; Hu, Zhi-Bin; Li, Chao-Jun
Abstract: During embryonic heart development, the progenitor cells in the epicardium would migrate and differentiate into noncardiomyocytes in myocardium and affect the integrity of ventricular wall, but the underlying mechanism has not been well studied. We have found that myocardium geranylgeranyl diphosphate synthase (Ggpps), a metabolic enzyme for cholesterol biosynthesis, is critical for cardiac cytoarchitecture remodelling during heart development. Here, we further reveal that epicardial Ggpps could also regulate ventricular wall architecture integrity. Epicardium-specific deletion of Ggpps before embryonic day 10.5 (E10.5) is embryonic lethal, whereas after E13.5 is survival but with defects in the epicardium and ventricular wall structure. Ggpps deficiency in the epicardium enhances the proliferation of epicardial cells and disrupts cell‒cell contact, which makes epicardial cells easier to invade into ventricular wall. Thus, the fibroblast proliferation and coronary formation in myocardium were found enhanced that might disturb the coronary vasculature remodelling and ventricular wall integrity. These processes might be associated with the activation of YAP signalling, whose nuclear distribution is blocked by Ggpps deletion. In conclusion, our findings reveal a potential link between the cholesterol metabolism and heart epicardium and myocardium development in mammals, which might provide a new view of the cause for congenital heart diseases and potential therapeutic target in pathological cardiac conditions.